Mycelial Growth and Fructification of Earwood Mushroom (Auricularia polytricha) on Different Substrates - Zurbano, L Y (KnE Social Sciences, 2018)
Auricularia polytricha is wood-rotting mushroom known as one of the edible mushrooms in the world recognized for its nutraceutical and pharmaceutical properties. To domesticate this species, the most favorable conditions for its mycelial growth and yield was evaluated in various culture media, grain spawn and fruiting substrates. The results revealed that A. polytricha cultured in coconut water gelatin (CWG) had the fastest mycelial ramification (6.33 days), growth rate (13.17 mm/day) and had the thickest mycelial growth. For spawn grain production, mycelial run on sweet sorghum grains was fastest at 5.0 days, had the highest growth rate at 16 mm/day and had the thickest mycelia. For fruiting bodies production, combination of good lumber sawdust, rice bran and lime (GLS:RB:L) had the fastest mycelial run at 30.33 days, highest growth rate (10.0 mm/day), yield (254.0 g) and biological efficiency (30.79%). Keywords: Auricularia polytricha, culture media, grain spawn, fruiting substrates, domestication